2021
DOI: 10.2147/tcrm.s322341
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Free PN is Associated with an Increased Risk of Hyperbilirubinemia in Surgical Critically Ill Patients with Admission Hepatic Disorder: A Retrospective Observational Study

Abstract: Background To evaluate the effect of different PN types on surgical critically ill trauma/acute care surgery patients with hepatic disorders at admission. Methods This is a retrospective study. The PN types included lipid-free, soybean oil/medium-chain triglyceride, olive oil-based, and fish oil-containing PNs. Patients admitted with liver injury or liver surgery, elevated serum AST/ALT level, and elevated serum total bilirubin level were included. The exclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Compared to the lipid-free group, the olive oil group had a lower risk of hyperbilirubinemia. In addition, the olive oil group had a significantly lower risk of mortality, while fish oil > 0.05 g/kg/day was associated with a lower incidence of liver dysfunction [13,14].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared to the lipid-free group, the olive oil group had a lower risk of hyperbilirubinemia. In addition, the olive oil group had a significantly lower risk of mortality, while fish oil > 0.05 g/kg/day was associated with a lower incidence of liver dysfunction [13,14].…”
Section: Discussionmentioning
confidence: 94%
“…Cholestasis is the result of obstruction of the bile ducts or inappropriate secretion. It is manifested by an increase in the levels of alkaline phosphatase (ALP), γ-glutamyl transpeptidase (GGTP) and bilirubin [14,17]. The degree and severity of liver dysfunction can be classified based on organ features observed on radiological examinationultrasonography (USG), liver imaging with computed tomography, magnetic resonance imaging (MRI) and liver biopsy, which is the gold standard [17].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies between 1980 and 1996, before the strategy of permissive underfeeding gained traction, involved critically ill patients and suggested that those receiving PN without ILE had lower complication rates and equivalent mortality rates compared to those receiving PN with ILE [ 7 ]. On the other hand, a single-center study published in 2021 of a selected group of critically ill surgical patients with hepatic disorder reported the highest mortality rates for those treated with PN without lipids [ 8 ]. In addition, propofol, an anesthetic agent containing lipid as a solvent [ 9 ], is often used during mechanical ventilation, but, to our knowledge, there have been no studies of the effects of ILE on clinical outcomes in critically ill patients that have taken propofol into consideration.…”
Section: Introductionmentioning
confidence: 99%